Carbonic Anhydrase 5 Regulates Acid-Base Homeostasis in Zebrafish - Postel, Ruben; Sonnenberg, Arnoud (PLOS ONE, 2012)
The regulation of the acid-base balance in cells is essential for proper cellular homeostasis. Disturbed acid-base balance directly affects cellular physiology, which often results in various pathological conditions. In every living organism, the protein family of carbonic anhydrases regulate a broad variety of homeostatic processes. Here we describe the identification, mapping and cloning of a zebrafish carbonic anhydrase 5 (ca5) mutation, collapse of fins (cof), which causes initially a collapse of the medial fins followed by necrosis and rapid degeneration of the embryo. These phenotypical characteristics can be mimicked in wild-type embryos by acetazolamide treatment, suggesting that CA5 activity in zebrafish is essential for a proper development. In addition we show that CA5 regulates acid-base balance during embryonic development, since lowering the pH can compensate for the loss of CA5 activity. Identification of selective modulators of CA5 activity could have a major impact on the development of new therapeutics involved in the treatment of a variety of disorders.